SUMMER CAMPS AND CANTONMENTS: A PROPOSAL OF ENVIRONMENTAL EDUCATION ON PRIVATE SCHOOLS (Fiep Bulletin - online, 2016)
For the children, the season in camps and cantonments are synonymous of new friendships, contact with funny monitors and laughs. For the parents, this period is the guarantee that their children will spend energy, learn to live in groups and discover new interests. We cannot forget about the respect of individual to the environment, providing opportunities values ??that will lead to a harmonious coexistence with nature and other species that inhabit it. Therefore, this study aimed to verify if the private schools that offer summer camps and cantonments simultaneously promote the leisure activities an environmental awareness. This study is characterized as a field descriptive research, held in three private schools in the city of Cascavel - PR. The data was collected with a questionnaire with five questions, two opened and three closed. The questionnaires were applied among the coordinators of the selected central schools. Through the results, we could observed that the camps and cantonments promoted by the schools, helped, indirectly, an environmental awareness with the students, since the initial intention is to promote leisure activities. However, in the "disengagement" of leisure camps, conditions are created to promote critical-reflexive consciousness related to the environment in which they live. However, it is understood that the strategies developed by the schools can be improved through careful planning and guidance of committed professionals with skills aimed at environmental education trough summer camps and leisure cantonments. Among these professionals, should be included a professional of Physical education.
Keywords: Summer camp. Environmental awareness. Leisure.